Peningkatan Yield Departemen XYZ pada PT X - Benedictus Rahardjo; Jani Rahardjo (Jurnal Titra, 2013)
XYZ Department at PT X didn’t achieve the yield target, which is one of the Key Performance Indicators, had been determined by Factory in 2012. Some improvements have been developed to increase yield in order to achieve the target. One of the improvements is to verify material transaction between two departments. Another improvement is to reduce the waste, from both Direct Incoming Material (DIM) and non DIM. DIM discussed in this research and contributing the top three waste materials in 2012, were filter rod, cigarette paper, and tipping paper. Non DIM waste that also gave contribution for increasing yield was tobacco. Yield has already increased by doing some of those improvements by 0.45% for AAA product, from 94.85% to 95.3%. Although the target of this year (95.4%) has not been achieved yet, these research’s results show yield increasing trend. In order to keep the consistency of the yield achievement, this Department made bulletin forms as standardization attached on the relevant machines. This bulletin form can be a standard operating procedure for those who operate that machine every day, so that the yield achievement can be stable and increase.